2015
DOI: 10.1507/endocrj.ej15-0131
|View full text |Cite
|
Sign up to set email alerts
|

TSH resistance revisited [Review]

Abstract: Abstract. Genetic defects of hormone receptors are the most common form of end-organ hormone resistance. One example of such defects is TSH resistance, which is caused by biallelic inactivating mutations in the TSH receptor gene (TSHR). TSH, a master regulator of thyroid functions, affects virtually all cellular processes involving thyroid hormone production, including thyroidal iodine uptake, thyroglobulin iodination, reuptake of iodinated thyroglobulin and thyroid cell growth. Resistance to TSH results in de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 19 publications
2
9
0
Order By: Relevance
“…Our study documents a 30% prevalence of inactivating TSHR mutations in a pediatric SCH population (34/111). This percentage is similar to that reported in literature …”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our study documents a 30% prevalence of inactivating TSHR mutations in a pediatric SCH population (34/111). This percentage is similar to that reported in literature …”
Section: Discussionsupporting
confidence: 92%
“…Previous studies that analyzed the rate of TSHR mutations in SCH populations reported highly variable frequencies (11%‐29%), with the highest prevalence occurring in consanguineous populations . Our study documents a 30% prevalence of inactivating TSHR mutations in a pediatric SCH population (34/111).…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…In case of biallelic variants, patients can have complete RTSH, resulting in severe hypothyroidism. Patients with monoallelic mutations have a partial RTSH, which results in nonautoimmune SH [40]. To date, at least 68 loss-of-function mutations of the TSHR have been described [39] with a variable prevalence (11% to 29%) depending on the population tested [38, 41–44].…”
Section: Mild Hypothyroidism In Neonatesmentioning
confidence: 99%
“…Thyroid-stimulating hormone (TSH) is a peptide hormone synthetized and secreted by pituitary with fundamental importance for thyroid function and balance, affecting iodine uptake, thyroxine and triiodothyronine production and, as a consequence, whole body metabolism [1,2]. It acts through thyroid-stimulating hormone receptor (TSHr), a classical seven transmembrane G-protein coupled receptor [3], being usually coupled to Gαs, increasing cAMP production and activation of PKA or even to Gαq and either activating Ras/Raf/Mek/ Erk or PI3K/Akt signaling pathways [4].…”
Section: Introductionmentioning
confidence: 99%